Estrategias para la enseñanza de la lengua kichwa a los estudiantes de la Unidad Educativa Adolfo Kolping, Yaruquiés Riobamba. - Melchor, Muyulema Cocha (2021)
ABSTRACT The work analyzes how the strategies of the Kichwa language operate in the students of the “Adolfo Kolping; This reflection, by the constitutional postulate, establishes that Spanish is the official language of Ecuador and that Castilian, Kichwa, and Shuar are official languages of intercultural relations. The other ancestral languages are of authorized use for indigenous peoples in the areas where they live and in the terms established by law. Traditional tactics and theoretical references are proposed in an attached didactic guide. It is concluded that the strategies used by teachers are fundamental in the teaching of the Kichwa language. Therefore, they do not allow them to raise the quality and level of learning, nor do they assess language, culture, and worldview. The development and appropriate use of physical and digital teaching materials and strategies are proposed, contributing to the improvement and mastery of Kichwa. The applied methodology was deductive, which consisted in deducing conclusions from the supposed statements, called premises. It was also analytical since it allowed the study of each of its variables, bibliographic (books, magazines, articles), and the results of other, non-experimental investigations. The study originated from the description of the observed context. In summary, the qualitative and qualitative approaches were used. Finally, the survey was applied to three teachers from the educational institution who received the didactic guide. Key Words: Strategies, Teaching, Kichwa Language. Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 0603017708